Application of electrophoretic deposition to occlude dentinal tubules in vitro. (April 2018) - Zhang, Lu; Sun, Hualing; Yu, Jian; Yang, Hongye; Song, Fangfang; Huang, Cui
Abstract: Objectives: This study aims to apply electrophoretic deposition (EPD) for occlusion of dentinal tubules in vitro and investigate its effect on tubule occlusion and shear bond strength (SBS). Methods: Charged mesoporous silica nanoparticles (MSNs) were synthesized and characterized through field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), dynamic light scattering (DLS), and Fourier transform infrared (FT-IR) spectroscopy analyses. Thirty-nine sensitive dentin specimens were modeled and assigned randomly to three groups with different treatments ( n  = 13 each): group 1, immersion in the MSN suspension; and groups 2 and 3, anodic EPD with the specimen on the negative and positive electrode respectively. The effect of dentinal tubule occlusion was evaluated by dentin permeability test ( n  = 10 each) and FESEM examination ( n  = 3 each). Moreover, 18 specimens were grouped ( n  = 6 each) and treated in the same method. A resin stick was bonded onto each of the specimen using a self-etch adhesive (single bond universal) for SBS testing. Results: Negatively-charged MSNs were synthesized and characterized as small and well-dispersed particles. After the EPD treatment (group 3), the dentinal tubules were effectively occluded by MSNs, which infiltrated into the tubules at a depth of approximately 7–8 μm and tightly associated with the tubular inwalls. SBS was not significantly different among the three groups ( P  >  0.05). Conclusions: Synthesized MSNs were deposited into dentinal tubules by EPD treatment without compromising dentin bond strength. Clinical significance: Application of EPD is a new approach for occlusion of dentinal tubules and exhibits potential in the study of dentin hypersensitivity.